A Unique Approach to Teaching Co‐Listed Science Courses: "Forty Chances" for Improved Graduate Student Education. Issue 1 (28th September 2017) - DeSutter, T. M.; DeSutter, K. L.
Abstract : Core Ideas: Graduate students read, reflected, and discussed Forty Chances for a co‐listed course. Students learned about the importance of soil health to food security. Using trade books in graduate courses helps link research to global, human issues. The trade book Forty Chances: Finding Hope in a Hungry World was used as a requirement for graduate students enrolled in an undergraduate–graduate co‐listed course. Forty Chances describes the complexities of food insecurity with specific linkages to soil health. Students were required to read, reflect, participate in group discussions, and, at the end of the course, answer a feedback form. The use of andragogy and self‐directed learning methods allowed students to connect the factual and theory‐based information from the course to a human issue. Although trade books may not be a substitute for studying the sub‐disciplines of soil science (chemistry, physics, biology), the first author found that inclusion of a trade book may support the next generation of agricultural scientists to understand how soil health and human health are related. Impact Statement Using trade books, group discussions, and reflective writing can be a teaching method to link students' research to a human experience. As an example, Forty Chances was used to help students understand the importance that soil health has on food insecurity. After reading, discussing, and exploring the professional literature, more than 90% of students indicated an improved awareness of food insecurity and understood the importance that soil health has in helping combat food insecurity.